Mercury removal from petroleum based industries wastewater by Pseudomonas putida ATCC 49128 in membrane bioreactor - Abd. Aziz, Mohd Azoddein (2013)
Mercury is an extremely toxic pollutant that currently being emitted and distributed globally. Microbes have been used to solve environmental wastewater problems for many years. The objective of the study is to remove mercury from petrochemical wastewater using Pseudomonas putida (P. putida), ATCC 49128 in membrane bioreactor to enhance water quality to meet EQA – Industries Effluent 2011 requirements. The approach of this study is focused on the removal or reduction of mercury concentration including development studies of pure culture of P. putida and growth related parameters involved in designing the membrane bioreactor system. Furthermore, this research also provide an understanding of P. putida behavior in rehydrating freeze-dried growing method, growth parameters and optimum operating condition in membrane bioreactor. A field survey on mercury concentrations at several petroleum based industrial plants in Peninsular Malaysia revealed a maximum reading of 2318 ppb which is higher than the Department of Environmental (DOE), Malaysia requirement for Standard B (50 ppb). Hence, treatment study of P. putida on mercury contaminated wastewater was conducted at mercury concentration in the range of 1000 – 4000 ppb. Optimum operating conditions of 24 hours acclimatization time, 180 rpm of orbital shaker speed, temperature of 37oC, pH 7 and nutrient concentration of 8 g/L were identified for P. putida growth in a shaked flask. The overall percentage of mercury removal for sample with 4000 ppb mercury in bioreactor is 99.60% for the first 6 hours and 99.80% removal after the microfiltration membrane system. Microfiltration membrane enhanced further the treatment of the wastewater by retaining the P.putida from escaping during the release of treated wastewater, reducing the turbidity by 94.2% (5.32 NTU) and concentration of suspended solids up to 60.4%. (0.09 mg/L). It was identified that the mechanism of mercury detoxification in the membrane bioreactor was based on reduction of Hg2+ to non-toxic Hg0 by mercury reductase enzyme produced by P. putida. The findings from this study can be used as references for future application of petroleum based industries wastewater treatment as well as other industries related to mercury contamination in their wastewater treatment plant such as gold mining, chemical industries, agriculture etc.